2017
DOI: 10.1038/srep40707
|View full text |Cite
|
Sign up to set email alerts
|

De novo AML exhibits greater microenvironment dysregulation compared to AML with myelodysplasia-related changes

Abstract: The interaction between the bone marrow microenvironment and malignant hematopoietic cells can result in the protection of leukemia cells from chemotherapy in both myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). We, herein, characterized the changes in cytokine expression and the function of mesenchymal stromal cells (MSC) in patients with MDS, AML with myelodysplasia-related changes (MRC), a well-recognized clinical subtype of secondary AML, and de novo AML. We observed a significant inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 83 publications
(87 reference statements)
0
25
0
Order By: Relevance
“…IL-6 and its downstream signaling molecules are responsible for multidrug resistance (72). Similarly, changes in IL-32 levels can alter the chemical protective effects of cells on cytarabine-induced apoptosis (20). In this study, our co-culture experiments further implicated the role of IL-6 and IL-32 in the development of chemoresistance as mediated by CTGF and the BMP pathway (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 and its downstream signaling molecules are responsible for multidrug resistance (72). Similarly, changes in IL-32 levels can alter the chemical protective effects of cells on cytarabine-induced apoptosis (20). In this study, our co-culture experiments further implicated the role of IL-6 and IL-32 in the development of chemoresistance as mediated by CTGF and the BMP pathway (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…These defects in AML-MSCs are closely related to DNA methylation, transcriptional gene expression (18) and chromosomal aberrations (19). Additionally, compared with HD-MSCs, the significant changes in cytokines, such as interleukin (IL)-6 and IL-32 induced by AML-MSCs has been shown to be associated with chemoresistance (20). Collectively, the BMM constructed by AML-MSCs can be considered distinct from that of HD-MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Reikvam et al reported that primary AML cells co-cultured with healthy donor-derived MSCs induce an increment in IL-6 release into the media [91]. Furthermore, Lopes et al showed that the increased amount of IL-6 produced by MSCs is directly correlated with disease progression from myelodysplastic syndrome (MDS) to AML [92]. In contrast to this study, Kittang et al demonstrated that MDS patients display higher IL-6 production compared to healthy donors, but the authors did not find any correlation between IL-6 levels and progression to AML [93].…”
Section: Il-6 Pathwaymentioning
confidence: 99%
“…As a result, AML cells modify the behavior of niche cells to an AML‐prone nature, thereby suppressing normal hematopoiesis and inducing the dominant proliferation of AML cells. Thus, the bone marrow microenvironments of MDS → OL (AML‐MRC) and de novo AML were found to be completely different from the normal functions of niche cells . In MDS bone marrow, CD34‐positive/c‐kit‐positive cells are generally located in proximity to CXCL12‐positive cells and express the BCL‐2 protein, resulting in the suppression of apoptosis.…”
Section: Bone Marrow Microenvironment Of Myeloid Neoplasmsmentioning
confidence: 99%